Rapid climate action is needed: comparing heat vs. COVID-19-related mortality - Batibeniz, Fulden; Seneviratne, Sonia I; Jha, Srinidhi; Ribeiro, Andreia; Suarez Gutierrez, Laura; Raible, Christoph C; Malhotra, Avni; Armstrong, Ben; Bell, Michelle L; Lavigne, Eric; Gasparrini, Antonio; Guo, Yuming; et al. (Scientific reports, 2025)
The impacts of climate change on human health are often underestimated or perceived to be in a distant future. Here, we present the projected impacts of climate change in the context of COVID-19, a recent human health catastrophe. We compared projected heat mortality with COVID-19 deaths in 38 cities worldwide and found that in half of these cities, heat-related deaths could exceed annual COVID-19 deaths in less than ten years (at + 3.0 °C increase in global warming relative to preindustrial). In seven of these cities, heat mortality could exceed COVID-19 deaths in less than five years. Our results underscore the crucial need for climate action and for the integration of climate change into public health discourse and policy.
Keywords: vysoká teplota; klimatické změny; velkoměsta; Climate Change; Hot Temperature; lidé; Cities; Public Health; Humans; veřejné zdravotnictví; COVID-19; SARS-CoV-2